Six weeks of HIIT based on repeated 5-meter sprints vs. countermovement jumps: effects on physical performance among karate athletes. A pilot-study - Ojeda-Aravena, A.; Herrera-Valenzuela, T.; Garcia Garcia, J. M.; Ramirez-Campillo, R. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Background. The kumite section or karate kumite is characterized by high-intensity activity, including explosive actions. Problem and Aim.Determine the magnitude of the effect on the physical performance of karate athletes of the application of two protocols: HIIT-SPRINT and HIIT-JUMP performed at the beginning of a training session (20 minutes) for six weeks. Methods. Both the HIIT-JUMP and HIIT-SPRINT group underwent a six-week HIIT program, while the CONTROL group con-tinued with their regular karate training. The athletes performed the following tests: squat jump, countermovement jump, 5m and 10m line speed, change of direction, aerobic capacity and body composition.Results. Fat mass (kg) decreased in the HIIT-JUMP group (ES = -0.63), while the HIIT-SPRINT group reduced the percent of body fat (ES = -0.85). Jump height for the squat and countermovement jumps increased in the HIIT-SPRINT group (ES = 0.82 and 0.94, respectively) and 10-m test (ES = -1.14) and change in direction (ES = -0.60) times were reduced. The HIIT-JUMP group decreased their times for the 5-m and 10-m tests (ES = -0.97 and -1.07, respectively). The HIIT SPRINT group improved in the 5-m test compared to the CONTROL group (ES = 0.62). Conclusions. These results suggest that both HIIT modalities offer spe-cific adaptations, and could be considered as complementary to the training of athletes.